Alternative to traditional olive pomace oil extraction systems: Microwave-assisted solvent extraction of oil from wet olive pomace. (April 2017) - Yanık, Derya Koçak
Abstract: The microwave assisted solvent extraction parameters of olive pomace oil was investigated. The oil extracted was compared with that obtained by the conventional industrial extraction method in terms of yield and some physical and chemical properties. This is the first attempt to extract oil from wet olive pomace directly using a closed vessel pressurized microwave system. The individual and interaction effects of independent parameters on extraction yield were analyzed by using response surface methodology. The microwave power (150–300 W), irradiation time (5–20 min), solvent-to-sample ratio (2–10) were identified as significant independent variables. Optimum extraction conditions were 287 W, 16 min and 10:1 (solvent-to-sample ratio). The maximum oil yield obtained at these optimum conditions was 6.85 g/100 g dry matter. Although the wet olive pomace was processed in microwave extraction the yield of oil was higher than that of oil extracted by the conventional industrial extraction method from dry olive pomace. In addition, total phenolic content (985 mg caffeic acid/kg oil) and amount of tocopherols (278.07 mg/kg oil) were higher while peroxide value (17.8 meq O2 /kg oil) and polycyclic aromatic hydrocarbons content (0.44 μg benzo[α]pyrene/kg oil) were lower in microwave assisted solvent extraction compared to conventional industrial extraction method. Highlights: This is the first attempt to extract oil from wet olive pomace directly. The yield obtained by MASE in a shorter time was comparable to CE method. High quality oil was produced by MASE method.